The effect of surface hardening on the HQ 705 steel camshaft using static induction hardening and tempering method - Nugroho, Sri; Fitriyana, Deni Fajar; Ismail, Rifky; Nurcholis, Thesar Aditya; Cionita, Tezara; Siregar, Januar Parlaungan (Universitas Muhammadiyah Magelang, 2022)
Induction hardening (IH) is a popular choice for automotive components such as camshafts for its ability to harden portions of a component selectively. The camshaft will contact the tappet, connected to the rocker arm, to open and close the valve whenever the engine is running. This contact between the camshaft and the tappet causes wear on the camshaft surface. IH of the camshaft is required to improve wear resistance and service life, as well as core elasticity to absorb high torsional stresses. It is known that studies about IH on camshafts are still very limited. This study aims to determine the effect of the induction hardening and tempering treatment on the mechanical properties of the camshaft made of HQ 705 steel. The induction hardening carried out in this study uses different parameter settings such as heating time and output current. The camshaft specimen is hardened by static induction and then quenched in oil. The specimens are tempered after induction hardening with different temperatures and holding times to adjust the hardness level and reduce brittleness. Hardness, macro photographs, micrograph, and wear tests were conducted to determine the mechanical properties of the camshaft specimen after the induction hardening and tempering process. This study indicates that induction hardening with an output current of 747 A for 15 seconds followed by tempering at 150 °C for 15 seconds on specimen 1 produced the best mechanical properties. On the surface of these specimens found more martensite content while there was no microstructural change on the inside. The surface hardness of these specimens is 44 HRC (Rockwell C Hardness), while the inside is 26 HRC. Meanwhile, specific wear decreased by 45.45%.